2018
DOI: 10.1007/s12035-018-1385-1
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Vesicles Released by Glioblastoma Cells Stimulate Normal Astrocytes to Acquire a Tumor-Supportive Phenotype Via p53 and MYC Signaling Pathways

Abstract: The role of astrocytes is becoming increasingly important to understanding how glioblastoma (GBM) tumor cells diffusely invade the brain. Yet, little is known of the contribution of extracellular vesicle (EV) signaling in GBM/astrocyte interactions. We modeled GBM-EV signaling to normal astrocytes in vitro to assess whether this mode of intercellular communication could support GBM progression. EVs were isolated and characterized from three patient-derived GBM stem cells (NES … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
98
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(105 citation statements)
references
References 73 publications
5
98
1
1
Order By: Relevance
“…In a later study, Hallal et al [60] reported increased podosome formation and extracellular matrix degradation in astrocytes cultured with GBM-derived EVs. In addition, they showed that the proteome of astrocytes exposed to GBM-derived EVs presented significant modifications in signaling pathways involved in tumorigenesis, such as decreased TP53 and increased MYC.…”
Section: Effects On Astrocytesmentioning
confidence: 91%
See 2 more Smart Citations
“…In a later study, Hallal et al [60] reported increased podosome formation and extracellular matrix degradation in astrocytes cultured with GBM-derived EVs. In addition, they showed that the proteome of astrocytes exposed to GBM-derived EVs presented significant modifications in signaling pathways involved in tumorigenesis, such as decreased TP53 and increased MYC.…”
Section: Effects On Astrocytesmentioning
confidence: 91%
“…This messenger activates the astrocytic production of inflammatory cytokines such as interferon-α and tumor necrosis factor, which in turn induce the activation of STAT-1 and NF-κβ pathways in the brain's metastatic cells, thereby supporting tumor cell invasion and resistance to chemotherapy [58]. More recently, two articles have reported tumor-supportive effects of astrocytes driven by EVs released by GBMs [59,60]. Oushy et al demonstrated that astrocytes cultured with EVs from patient-derived GBMs display profound modifications of the secretome that results in positive effects on tumor growth [59].…”
Section: Effects On Astrocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…EVs are key messengers of intercellular communications that control the establishment and maintenance of TME [99], are actively secreted by GBM cells, and promote their oncogenic features [100][101][102][103]. For instance, GBM-secreted EVs stimulate recipient astrocytes to acquire a pro-tumoral phenotype by delivering several factors, including MYC and MYCN [101]. Furthermore, EV-mediated transfer of splicing factors from apoptotic to healthy GBM cells has also been proposed as a mechanism to alter splicing patterns and to promote malignancy.…”
Section: Tumor Microenvironmentmentioning
confidence: 99%
“…A range of GBM samples (EVs, cells and tumour tissue fractions) were used to generate a comprehensive, custom glioma IDA spectral library. Specimens were prepared as described before from neurosurgical aspirate EVs [24], patient-derived GBM-stem-like cells [50], and soluble and microsomal proteomes [51] prepared from GBM tumour tissue (Supplementary Table 2). The peptide samples were fractionated by HILIC, a reverse-phase chromatographic method, to reduce sample complexity and increase protein ID coverage by LC-MS/MS [52].…”
Section: Hydrophilic Interaction Liquid Chromatography (Hilic)mentioning
confidence: 99%